1997
DOI: 10.1046/j.1365-2141.1997.2423059.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of platelet‐specific autoantibodies in platelet eluates of ITP patients measured by a novel ELISA using the purified glycoprotein complexes GPIIb/IIIa and GPIb/IX as antigens

Abstract: Summary.Immune thrombocytopenic purpura (ITP) is a disorder caused by anti-platelet autoantibodies (Ab), most of which are directed against epitopes on platelet membrane glycoprotein complexes GPIIb/IIIa and GPIb/IX. To detect platelet Ab, reliable techniques, such as MAIPA or immunobead assay, have been developed. They all achieve their selective specificity by the use of monoclonal antibodies (MoAb) against defined glycoproteins of the platelet membrane. In order to determine the most frequent Abspecificitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…16 Platelet-associated and plasma IgG anti-GPIIb-IIIa antibodies IgG anti-GPIIb-IIIa antibodies in platelet eluates and plasma were measured in some samples using ELISA according to the method described elsewhere. 22 Platelet eluates were prepared by incubating the platelets with 0.1 mol/l HCl followed by immediate neutralization with 0.2 mol/l NaOH. Antibody units were calculated from the OD 450 results, based on a standard curve obtained from serial concentrations of pooled plasma with a high level of IgG anti-GPIIb-IIIa antibodies.…”
Section: Circulating B Cells Producing Igg Anti-gpiib-iiia Antibodiesmentioning
confidence: 99%
“…16 Platelet-associated and plasma IgG anti-GPIIb-IIIa antibodies IgG anti-GPIIb-IIIa antibodies in platelet eluates and plasma were measured in some samples using ELISA according to the method described elsewhere. 22 Platelet eluates were prepared by incubating the platelets with 0.1 mol/l HCl followed by immediate neutralization with 0.2 mol/l NaOH. Antibody units were calculated from the OD 450 results, based on a standard curve obtained from serial concentrations of pooled plasma with a high level of IgG anti-GPIIb-IIIa antibodies.…”
Section: Circulating B Cells Producing Igg Anti-gpiib-iiia Antibodiesmentioning
confidence: 99%
“…5,10 All samples were tested in duplicate, and the results were calculated as the duplicate mean. Cutoff values for plasma and platelet eluates were considered the mean plus 3 ϫ SD of 20 samples from healthy donors.…”
Section: Detection Of Anti-gpiib-iiia Antibodiesmentioning
confidence: 99%
“…1,2 These antibodies bind to circulating platelets, resulting in platelet destruction by the reticuloendothelial system. The major target of the antiplatelet autoantibodies is platelet membrane glycoprotein IIb-IIIa (GPIIb-IIIa), [3][4][5] also designated ␣ IIb ␤ 3 integrin or CD41/CD61, which is a calcium-dependent heterodimeric membrane receptor for fibrinogen and other ligands. 6 Although earlier studies reported the presence of plateletreactive T cells in patients with ITP, [7][8][9] we have recently found that GPIIb-IIIa is one of the major target antigens recognized by platelet-reactive CD4 ϩ T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Direct platelet eluates also allow detection of GP-specific PA-IgG and the results obtained are in good agreement with direct tests; in 82 ITP patients, the antibodies were shown to have specificities against both GP IIbIIIa (in up to 90%) and IbIX (less than 20%; Kiefel et al, 1996;Hürlimann-Forster et al, 1997; Table 4). Nevertheless, the detection of direct platelet eluates requires a selected patient population with a relatively high platelet count.…”
Section: Detection Of Gp-specific Pa-iggmentioning
confidence: 56%